Effects of Past and Present-Day Landscape Structure on Forest Soil Microorganisms - Mennicken, Sophie; Kondratow, Floriane; Buralli, Florian; Manzi, Sophie; Andrieu, Emilie; Roy, Mélanie; Brin, Antoine (Frontiers in Ecology and Evolution, 2020)
Theory surrounding landscape ecology have been built on the species distribution of birds and plants, but increasing evidence now exists for below-ground organisms, whose dispersal may also be affected by above-ground landscape structures. Uncertainties remain for how communities of microorganisms respond to landscape structure over time, and whether some groups of microorganisms react more than others. Here, we investigated if fungal or bacterial diversity is driven by the amount of forest cover in the current or the past landscape. We tested the Habitat Amount Hypothesis (HAH) on ancient forests of the Cevennes national park, that experienced increased fragmentation 150 years ago, and are today surrounded by recent forests. As ancient forests are often more diverse in plant species, we hypothesized that the higher quantity of ancient forests in the landscape, the richer local fungal and bacterial communities would be. More precisely, we expected that ectomycorrhizal fungi, and pathotrophic fungi, often indicators of mature forests, would be also more sensitive to forest history and therefore to the quantity of ancient forests than bacteria and saprotrophic fungi. We sampled 40 soil cores per 0.5 ha, pooled in 8 composite samples per plot in 27 landscapes and sequenced ITS and 16S markers by Illumina-Mi seq. To identify functional groups of fungi, we relied on their taxonomy and the use of public databases. Our results partly follow the HAH, as fungal richness was positively related with the quantity of ancient forests in the landscape and not by the focal patch size. Ectomycorrhizal and pathotrophic fungi were positively affected by the ancient forest cover, and so were saprotrophic ones, but not bacteria. Local factors also shaped the communities such as soil composition and elevation, confirming classical patterns in soil microbial ecology. Interestingly, past landscape structure was better at explaining fungal community richness than contemporary landscape, suggesting a time lag in the response of communities to landscape modification and a potential extinction debt. Our results reveal the importance of below-ground communities in studies of landscape and historical ecology, with their structure and functions likely to be intimately linked with soil and landscape history.